ANALYSIS OF THE CURRENT STATE OF DEVELOPMENT OF THE SECURITIES MARKET IN UZBEKISTAN - Shomirov Azizbek Abdurashidovich (American Journals, 2025)
The article examines issues related to current problems and trends in the development of the international securities market in the current unstable socio-economic conditions on the global stock market. It also touches upon issues related to the situation on the securities market in the Republic of Uzbekistan. The main factors influencing the development of the stock market, the main problems and possible solutions for the issue of securities are considered.
Keywords: Stock market, securities market, investments, emission, financial instruments.